Survei Kompetensi Guru terhadap Hasil Belajar Siswa Mata Pelajaran Matematika Kelas VIII SMPN 28 Surabaya - Amalia, Amalia; Meidina, Amanda Putri; Sekarsari, Irma Mei; Wulandari, Ayu (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2025)
Low mathematics learning outcomes among grade VIII students at SMPN 28 Surabaya are influenced by suboptimal teacher competence, as reflected in varied daily assessment scores and national PISA surveys. This study aims to analyze the relationship between teacher competence and students' mathematics learning outcomes through a correlation survey. Quantitative approach with survey method applied; population all grade VIII students, sample 57 students from classes VIII-I and VIII-J via purposive sampling. Instruments: 41-item Likert questionnaire (valid and reliable, Cronbach's Alpha 0.952), secondary data from daily assessment scores, non-parametric Spearman Rho analysis after normality test failure (Sig. 0.005).​ Results indicate very weak correlation (rho 0.038) and non-significant (Sig. 0.781). The study concludes that teacher competence is not the primary determinant of mathematics learning outcomes, recommending holistic approaches including student motivation.